PENGEMBANGAN PRODUK SALA LAUAKDENGAN TEKNIK GELATINISASI - Dwi, Elfrimo; Faridah, Anni; ., Ernawati (Universitas Pendidikan Ganesha, 2019)
Sala lauak is a traditional food that is easily found in West Sumatra. The development of sala leak products is carried out by reducing oil using gelatinization techniques. The process that occurs in gelatinization is when the starch granules are given water and heat, the starch granules will expand. This study aims to (1) develop sala lauak products by gelatinization techniques on oil absorption, (2) determine the organoleptic quality of sala lauak products by gelatinization technique processes, and (3) determine the fat content of sala lauak products by gelatinization technique processes. This research method is Research and Development (RnD). The results of this study in the organoleptic quality produced by sala lauak with pragelatinization flour showed a significant influence on the quality of inner texture, outer texture, taste, shape, and color. The same thing also happened to a significant reduction in fat content by three times lower using pregelatinized rice flour which is 7.4% compared to ordinary rice flour which is 25%.Â Kata kunciÂ : Â Sala Lauak, Gelatinization Technique, rice flour.